(untitled) (Педагогіка вищої та середньої школи, 2010)
In this article is considered methodological and competence aspects, scientific management issues of universities, which can be qualified as regional. Functional and competence model of regional university is formed. It presents values and parameters of education, science, technology and innovation activities, competence profiles for students according to regional needs.